THE ROLE OF INSTRUCTION IN ENGLISH GRAMMAR TEACHING/O PAPEL DA INSTRUÇÃO NO ENSINO DA GRAMÁTICA DO INGLÊS - Bezerra (UnB), Emanuela dos Santos; Bergsleithner (UnB), Joara Martin (Revista ECOS, 2021)
This study aims at discussing some types of grammar instructions in the teaching of English as an L2. Furthermore, it aims at showing how the teacher might call learners’ attention to their grammatical errors in order to raise their consciousness, through negotiation of grammatical aspects, as well by means of feedback strategies. Finally, a discussion of how different the kinds of instruction might contribute to the L2 teaching/learning process will be presented.